1997
DOI: 10.1083/jcb.136.6.1201
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Nuclear Lamin Organization Alters the Distribution of Replication Factors and Inhibits DNA Synthesis

Abstract: The nuclear lamina is a fibrous structure that lies at the interface between the nuclear envelope and the nucleoplasm. The major proteins comprising the lamina, the nuclear lamins, are also found in foci in the nucleoplasm, distinct from the peripheral lamina. The nuclear lamins have been associated with a number of processes in the nucleus, including DNA replication. To further characterize the specific role of lamins in DNA replication, we have used a truncated human lamin as a dominant negative mutant to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
236
1
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(263 citation statements)
references
References 60 publications
20
236
1
6
Order By: Relevance
“…Previous studies demonstrated that disruption of lamin organization by a dominant-negative lamin A mutant (ΔNLA), missing the first 33 amino acids of human lamin A, repressed DNA replication. This was associated with the redistribution of DNA replication proteins RFC and PCNA away from chromatin to form nuclear aggregates along with the nuclear lamins (37). In addition, accumulation of prelamin A has been shown to interfere with PCNA function and cause replication stress (9).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that disruption of lamin organization by a dominant-negative lamin A mutant (ΔNLA), missing the first 33 amino acids of human lamin A, repressed DNA replication. This was associated with the redistribution of DNA replication proteins RFC and PCNA away from chromatin to form nuclear aggregates along with the nuclear lamins (37). In addition, accumulation of prelamin A has been shown to interfere with PCNA function and cause replication stress (9).…”
Section: Resultsmentioning
confidence: 99%
“…A-type lamins have also been found in association with transcription factors (Dreuillet et al, 2002;Lloyd et al, 2002). Furthermore, disruption of normal lamin organization by microinjection of a dominant-negative lamin A mutant results in inhibition of both DNA replication (Spann et al, 1997) and RNA polymerase II-dependent transcription (Spann et al, 2002) suggesting a role for lamin A in both these processes. Finally, lamins have the ability to bind directly to DNA (Stierle et al, 2003) and to chromatin (Glass et al, 1993;Taniura et al, 1995) and indirectly via associations with proteins containing a LEM box (Lee et al, 2001;Martins et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The proteins expressed by using this vector contained an N-terminal His 6 tag followed by 6 kDa of laminin rod (38). The lamin fragments were expressed in NovaBlue DE3 bacteria cotransfected with pLys-S (Novagen) and induced with 1 mM isopropyl ␤-D-thiogalactoside for 2-4 h. The protein fragments were solubilized from inclusion bodies in column buffer (6 M urea͞10 mM Tris⅐HCl, pH 8.0͞10 mM DTT͞2 mM EDTA), purified on a Mono Q column by FPLC (Amersham Pharmacia), and eluted in column buffer containing 0-1.0 M NaCl (11). Column fractions containing the lamin fragments were identified by SDS͞PAGE and either dialyzed into PB or further purified by using nitrilotriacetic acid-agarose (Qiagen) and then dialyzed into PB.…”
Section: Bacterial Expression and Purification Of Wild-type And Mutanmentioning
confidence: 99%
“…Nuclei were suspended in NWB, fixed with either 2% ethylene glycol bis(succinimidylsuccinate) (Pierce) or 2.0% formaldehyde for 10 min, and spun onto poly(L-lysine)-coated coverslips through 20% sucrose in NWB, as described in ref. 11. The coverslips were washed with PBS containing 0.1% Nonidet P-40, washed again with PBS, and overlayed with primary Abs diluted 1:200 (11).…”
Section: Bacterial Expression and Purification Of Wild-type And Mutanmentioning
confidence: 99%